Bees algorithm for solving minimum routing cost spanning tree problem. - Quoc, Phan Tan; Nghia, Nguyen Duc (Journal of Computer Science and Cybernetics, 2013)
The task to find Minimum Routing Cost Spanning Tree (MRCST) can be found in many network design problems. In general cases, the MRCST problem is proved to be NP-hard. This paper proposes an algorithm tosolve MRCST problem based on the schema of bee algorithm. The computationa lexperiment results show that our proposed algorithm outperforms the Wong’s algorithm, population-basedmeta-heuristics like Max-Min Ant System (MMAS), Genetic Algorithm (GA), Artificial Bee Colony algorithm (ABC), and other well-known heuristic algorithms. The cost to get this result is the large number of spanning trees examined by our algorithm compared to other methods, e.g., 16000 times and 1.7 times more than that of Wong’s algorithm and ABC algorithm on average, respectively.